2017
DOI: 10.1111/ped.13305
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of infantile food protein‐induced enterocolitis syndrome in Japan

Abstract: Background: Although serum C-reactive protein (CRP) and the percentage of eosinophils in peripheral blood (Eo) are increased at onset in infants with food protein-induced enterocolitis syndrome (FPIES), the relationship of these laboratory findings to prognosis is presently unknown. Methods: Correlation of serum CRP and Eo at onset with prognosis was analyzed in 32 patients with FPIES caused by cow's milk (CM).Results: The rate of tolerance acquisition was 18.8%, 56.3%, 87.5%, and 96.9% at the ages of 6, 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…1,20 Recently, eosinophilia in infantile FPIES was reported to be transient and associated with good prognosis. 21 Thus, eosinophilia is unlikely to have deleterious effects on the GI system in patients with FPIES.…”
Section: Discussionmentioning
confidence: 99%
“…1,20 Recently, eosinophilia in infantile FPIES was reported to be transient and associated with good prognosis. 21 Thus, eosinophilia is unlikely to have deleterious effects on the GI system in patients with FPIES.…”
Section: Discussionmentioning
confidence: 99%
“…11,[19][20][21][22] In Korea, cow's milk is the most common causative food. 23 In Japan, milk was the causative food of most FPIES until 10 years ago, 24,25 but reports of FPIES caused by hen's eggs have been increasing since 2016. 10,16,26 Furthermore, the primary antigen for FPIES caused by hen's egg was egg yolk, not egg white.…”
Section: Food Triggersmentioning
confidence: 99%
“…The onset of FPIES caused by solid foods such as rice, hen's egg, or fish is from 5 to 12 months of age. 5,12 The age of onset of FPIES caused by milk varies by country, ranging from approximately 1 month in Japan and Korea 23,25 to 3-5 months in the United States, Italy, and Australia. 5,40,41 The reason for the difference in the age of onset of patients with milk-induced FPIES in Asian and Western countries is unknown, but this difference may be a factor in the high prevalence of chronic FPIES in Japan and Korea.…”
Section: Age Of Onsetmentioning
confidence: 99%
“…Kimura et al [60] recently studied 32 patients with FPIES caused by CM and found a significant positive correlation [15] between the time of acquisition of tolerance and the level of serum C-reactive protein at onset and a significant negative correlation with the percentage of eosinophils in peripheral blood at onset, thus suggesting that C-reactive protein could be a useful parameter of poor prognosis and that eosinophilia could be used as a marker of good prognosis.…”
Section: Long-term Management and Prognosismentioning
confidence: 99%